(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The article addresses the issue of identity and identitarianism within the realm of political struggle based on and guided by representativity. We start by examining the problematics of identitarianism as a means through which individuals organize their actions in contemporary political collectivities, considering the central ideas of Haider (2019) and Butler (2018a, 2018b). The research aims to understand why identity becomes a problematic marker for the success of social groups’ achievements. Keywords: identity; identitarianism; alliances; performativity.